Integrating legume-based systems into wheat monoculture: Agronomic and soil fertility impacts in the southeastern highlands of Ethiopia - Mesfin, Tewodros; Tibebe, Degefie; Abera, Wuletawu; Liben, Feyera; Mkuhlani, Siyabusa; Kouadio, Amani Louis (Bioversity International and International Center for Tropical Agriculture, 2025)
Wheat production in Ethiopia’s Bale highlands is central to national food security but is increasingly constrained by interannual climate variability, soil fertility decline, and competing demands for crop residues in mixed crop–livestock systems. To evaluate sustainable intensification pathways, we applied APSIM Classic (v7.10) within the AgWise framework to simulate long-term (1994–2024) performance of wheat monoculture and legume-integrated alternatives across a 10 × 10 km grid in Bale Zone, southeastern Oromia, Ethiopia, using gridded rainfall (CHIRPS), temperature (ERA5), solar radiation (NASA POWER), and 10-km soil profile data. Three wheat-based systems were assessed: continuous wheat, a wheat–faba bean rotation, and a field pea–wheat double-cropping sequence, with legumes simulated under 0 and 25 kg N ha⁻¹ starter N while wheat management was held constant (80 kg N ha⁻¹ split and 15 kg P ha⁻¹ per crop). System performance was quantified using annual system grain yield, interannual variability (CV), downside risk (years with yield <300 kg ha⁻¹), and soil indicators (organic carbon and profile NO₃–N). Legume integration generated strong spatially structured yield responses: the faba bean–wheat rotation supported by starter N produced the greatest yield potential and the largest site-to-site heterogeneity, including extreme high-yield outliers, whereas unfertilized double cropping frequently incurred a yield penalty. Nitrogen supply to the legume phase was pivotal for risk outcomes: unfertilized double cropping showed the highest yield instability and downside risk, while starter N reduced variability and shifted downside risk toward levels comparable to continuous wheat. Across systems, simulated soil organic carbon was higher under legume-based diversification than under continuous wheat, while elevated and slowly increasing profile NO₃–N was largely confined to the fertilized faba bean–wheat rotation. These results support spatially targeted promotion of legume–wheat systems, emphasizing modest starter N to legumes to maximize productivity while limiting downside risk under highland conditions.